The role of organ- and function-preserving radiotherapy in the treatment of adenoid cystic carcinoma of the larynx - Akbaba, Sati; Uzun-Lang, Kristin; Bulut, Cem; Held, Thomas; Rieken, Stefan; Plinkert, Peter K.; Jensen, Alexandra; Herfarth, Klaus; Debus, Jürgen; Adeberg, Sebastian (Head & neck, 2019)
BACKGROUND: To evaluate clinical outcome and functional larynx preservation after radiotherapy (RT) for adenoid cystic carcinoma (ACC) of the larynx. - METHODS: Eleven patients with primary ACC of the larynx, who received RT definitely (n = 5/11) or postoperatively (n = 6/11), were analyzed regarding survival and treatment-related toxicity with the focus on functional larynx preservation. - RESULTS: Median follow-up was 45 months. RT offered an excellent 5-year local control (LC) rate of 100%. Eight of 11 patients were treated with a laryngeal preservation approach (LPA). At last follow-up, only one of these eight patients developed a local recurrence requiring a total laryngectomy 11 years after treatment. Severe toxicity was uncommon, with only one patient with LPA, requiring a temporary tracheostomy during therapy. - CONCLUSIONS: RT is an effective treatment method for laryngeal ACC with excellent LC rates, preservation of the laryngeal function and voice formation, representing a valuable therapy alternative to total laryngectomy.